Judge Leonard Meyers Retirement Luncheon at Golden State Plaza Ballroom - Watkins, Howard::::::::: (1987)
Fresno County Bar Association President Howard Watkins, Supervisor Bruce Bronzan, Samuel Palmer III, Max Hayden seated at head table; Judge Stephen Henry speaking at lectern